Al-Qur'an Sebagai Kitab Pendidikan - Syamsi Husnidar Tamba (Jurnal Studi Pesantren, 2024)
Islam is a perfect religion that regulates all aspects of human life. Religion regulates education, physical and spiritual health, Islam is not just about human spirituality, Islam also regulates social society. Only the Islamic religion discusses all aspects of human life in detail and detail. God's messages conveyed to humans through the apostles contain educational elements. Educational theories in the Al-Qur'an can be studied through the verses of the Al-Qur'an which are used as references. In the content of these Al-Qur'an verses, Allah SWT has given the five senses as the main capital. Meanwhile, in the hadith, educational theory is developed through human nature (potential). This research uses a library research method, namely a method of collecting data from various relevant sources; through books, journals/articles, research that discusses or examines this study previously.